Not the best fillers in of forms? The Danish and Norwegian graduate biographies and "upper tail knowledge" - Nicholas Martin Ford; Kristin Ranestad; Paul Sharp (European Historical Economics Society (EHES), 2023)
'Upper tail knowledge', embodied by knowledge elites, has been suggested to be a driving force of industrialization and development, yet measuring it remains problematic. Despite some recent innovations, much empirical work continues to rely on measures of 'average' or 'non-upper tail' human capital such as literacy and years of schooling. We thus turn to perhaps unique sources from Denmark and Norway. From the early nineteenth century until after the Second World War, these countries had the tradition of publishing biographies of all high school graduates, usually 25 and 50 years after graduation. These were effectively mini-CVs covering entire careers, including work positions, travel, achievements, and more. We discuss these sources and their potential for furthering our understanding of the role of upper tail knowledge and human capital for development. Source criticism reveals strengths and weaknesses, but importantly confirms promising perspectives for improving the measurement of upper tail knowledge.
Keywords: E24; I20; J24; N33; N34; 330; Biographies; Denmark; Norway; human capital; source criticism; upper tail knowledge